Peptidomic analysis of mycobacterial secreted proteins enables species identification. Issue 4 (18th April 2022) - Shu, Qingbo; Rajagopal, Meena; Fan, Jia; Zhan, Lingpeng; Kong, Xiangxing; He, Yifan; Rotcheewaphan, Suwatchareeporn; Lyon, Christopher J.; Sha, Wei; Zelazny, Adrian M.; Hu, Tony
Abstract: Pulmonary disease arising from slow‐growing mycobacterial infections has emerged as an increasingly prevalent clinical concern over the past two to three decades. Proteins belonging to the family of ESAT‐6 secretion (Esx) systems play critical roles in the virulence of most pathogenic mycobacterial species and are associated with drug resistance. However, no clinical applications can detect and discriminate the expression of species‐specific variants of these proteins in clinical samples, such as early growth cultures, for rapid diagnosis of specific mycobacterial infections, which may require distinct interventions. Conventional immunoassay approaches are not suitable for this purpose due to the significant degree of conservation of Esx proteins among species. Herein we describe the development of a novel immunoprecipitation‐coupled mass spectrometry assay that can distinguish Esx proteins that are expressed by slow‐growing mycobacterial species commonly detected in clinical isolates. This approach uses custom antibodies raised against single semi‐conserved peptide regions in M. tuberculosis ( Mtb ) EsxB and EsxN to capture corresponding peptides from protein orthologs of mycobacteria associated with human respiratory infections, including Mtb, M. avium, M. intracellulare, M. kansasii, M. gordonae, and M. marinum, to detect these species in standard clinical cultures at the first sign mycobacterial growth to allow rapid disease diagnosis. Abstract : A PRM‐MS based method is proposed to identify conserved peptide regions of CFP‐10 and EsxN from slow‐growing mycobacteria species that cause human diseases. Using pan‐peptide variant antibody, peptide variants with minor amino acid variation can be captured simultaneously to aid in species identification at the time to positivity of MGIT samples.